Misi Evangelisasi: Beberapa Catatan dalam Kerangka Teologi Alkitabiah dan Dogmatik - Sudhiarsa, Raymundus I Made (Perspektif, 2014)
Mission evangelization is at the heart of the Church, since ‘the pilgrim Church is missionary by her very nature’ (AG 2; LG 1). It logically means that mission cannot be treated as a function among other tasks God has entrusted to his people, the Church. This article tries to present a general analysis on the concept of mission evangelization based on the biblical grand narrative and doctrine of the Church since Vatican II. Mission of the Church, which characterises the Church as missional community, originates from God’s mission (missio Dei) – mission of the Most Holy Trinity: God the Father sent the Son, and God the Father and the Son sent the Spirit. It would describe that mission essentially has a Trinitarian foundation as well as a Christological, Soteriological, and Pneumatological foundation. Since the Church is the seed, sign and instrument of God’s kingdom, surely mission also has an ecclesiological foundation. From the biblical grand narrative, mission derives four theological themes: creation, fall, redemption, and eschatological restoration. From these four plot movements, focusing on God’s mission, the Church is called and sent to participate actively. Mission of the Church, therefore, is basically a ‘participation in and representation of’ the mission of God.